若m^2+n^2-6n+4m+13=0则m-n=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 18:52:03
若m^2+n^2-6n+4m+13=0则m-n=?若m^2+n^2-6n+4m+13=0则m-n=?若m^2+n^2-6n+4m+13=0则m-n=?m²+²-6n+4m+13=0
若m^2+n^2-6n+4m+13=0则m-n=?
若m^2+n^2-6n+4m+13=0则m-n=?
若m^2+n^2-6n+4m+13=0则m-n=?
m²+²-6n+4m+13=0
(m²+4m+4)+(n²-6n+9)=0
(m+2)²+(n-3)²=0
两非负数和为0,故(m+2)²=0且(n-3)²=0
所以m=-2,n=3
m-n=-5
m^2+n^2-6n+4m+13=0
(m²+4m+4)+(n²-6n+9)=0
(m+2)²+(n-3)²=0
∴m=-2;n=3
来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来来
若m^2+n^2-6n+4m+13=0则m-n=?
若m×m+n×n-6n+4m+13=0,则m×m-n×n=?
m^2+4m+n^2-6n+13=0,则m+n=
若x^2+n^2—6n+4m+13=0,则m-n
若m^2+n^2-6n+4m+13=0,则m^2-n^2=?
若m^2+n^2-6n+4n+13=0,则m^2-n^2=
若m平方+n平方-6n+4m+13=0,则(m+n)(m-n)=?
m^2+n^2=6n-4m-13,则m^2-n^2=?
若m^2+n^2+2m-4n+5=0,则m+n=?
已知3m=4n,则m/m+n+n/m-n-m^2/m^2-n^2=
若m^2+n^2-6n+4m+13=0,m^2-n^2=?v
若m^2+n^2=6n-4m-13,则m^2-n^2=( )
若m^2+n^2=6n-4m-13,则m^2-n^2=()
m^2+n^2-6n+4m+13=0,则m^2-n^2=
已知实数m,n,且m>n>0,m²+n²=4mn,则m²﹣n²/mn的值等于∵(m+n)²=m²+2mn+n²,(m-n)²=m²-2mn+n²,m²+n²=4mn.(m+n)²=6mn(m-n)²=2mn(m+n)²(m-n)²=12m²n²mm³-2m
若|m|=4,|n|=1/2 1,若m+n>m-n,则m+n=?2,若|m+n|=|m|+|n|若|m|=4,|n|=1/21,若m+n>m-n,则m+n=?2,若|m+n|=|m|+|n|,则m、n的值分别是:
1若m=n,则|m|=|n|;2若m=—n,则|m|=|n|;3若|m|=|n|,则m=—n;4若|m|=|n|,则m=n哪个对
若(m-2n)/(2m+n)=3,则[3(m-2n)/(2m+n)-(m-2n)/[2(2m+n)] - {9(m-2n)/[4(2m+n)]}的值是?